Pemberdayaan ibu rumah tangga di Kelurahan Kalibaru, Cilincing Jakarta Utara melalui kegiatan Pengabdian Kepada Masyarakat UTA’45 Jakarta - Khoirunnisa, Khoirunnisa; Hidajat, Koerniawan; Rahmadan, Yanuar; Nabila, Firdiyatul; Juniaty, Risnawaty; Sari, Nilam (Jurnal Pemberdayaan Nusantara, 2023)
The processing of small fish into fish sauce is an innovative process in the sustainable utilization of fisheries resources. Groundfish, which is generally considered as waste fish -as it does not have high economic value, can be transformed into value-added products such as fish sauce. This study aims to explore and develop the production process of fish sauce from low-cost fish, as well as to analyse the economic potential of this low-cost fish. The research method involves the stages of selecting suitable low-cost fish, processing the fish into soy sauce raw materials, and making fish sauce through fermentation. The economic analysis involved estimating production costs, selling prices, and potential profits. The Kalibaru Subdistrict, Cilincing, North Jakarta has great potential in the development of the fisheries sector. To improve the sustainability of fisheries in this area, innovation is key. One of the potentials from the Kalibaru Subdistrict is groundfish. The processing of raw fish into fish sauce allows for a more efficient and sustainable utilization of fishery resources. The fermentation process not only increases the nutritional value of fish sauce but also provides economic sustainability for local communities. In addition, involving housewives provides a positive impact on local economic empowerment and increases awareness of the value-added potential of fishery products.